1999
DOI: 10.1161/01.hyp.34.5.1060
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Systolic Pressure Variability During Atrial Fibrillation and Sinus Rhythm

Abstract: Abstract-Previous studies have found that respiratory variations of ventricular response in atrial fibrillation are infrequent and inconsistent. This asynchrony between heart rate and respiration may characterize the physiological mechanisms coupling heart rate and systolic blood pressure oscillations in the respiratory band. The aim of this study was to evaluate whether synchronous variations in systolic blood pressure and respiration depend on a simultaneous change in heart rate. Univariate and bivariate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…This clear evidence distinguishes atrial flutter from atrial fibrillation, where the irregularity of the rhythm prevails over respiratory patterning and even the presence of respiratory arrhythmia is a matter of debate (10,20,39,46,51). In atrial flutter, the simple reentrant mechanism underlying atrial activation determines a more regular rhythm, which makes the respiratory modulation apparent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This clear evidence distinguishes atrial flutter from atrial fibrillation, where the irregularity of the rhythm prevails over respiratory patterning and even the presence of respiratory arrhythmia is a matter of debate (10,20,39,46,51). In atrial flutter, the simple reentrant mechanism underlying atrial activation determines a more regular rhythm, which makes the respiratory modulation apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, frequencydomain techniques have been applied to a less extent in the characterization of cardiovascular oscillations during atrial arrhythmias (50,54,59). Spectral and cross-spectral analyses have been applied to individuate the presence of a respiratory modulation of heart rate and blood pressure in atrial fibrillation (23,46), whereas spectral analysis has been used to characterize the overall variability of atrial flutter cycle length (50,59). Focusing on the respiratory modulation of atrial flutter rhythms, in the present study we applied cross-spectral analysis to both atrial and ventricular interval series to test effectively the presence of coupling between atrial/ventricular series and respiration and to characterize the phase relation of the interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the highly irregular heart rate, the beat-to-beat variation of blood pressure is increased because of variations in filling time and in contractility. Only a few studies [4,14,15] have evaluated whether rhythmical components could be identified in short-term heart rate and systolic arterial pressure (SAP) variability during AF.…”
Section: Introductionmentioning
confidence: 99%
“…A respiratory-related HF component of systolic blood pressure variability has been observed during AF even in absence of a respiratory sinus arrhythmia of the RR series [14]. However, there is lack of information on the possible existence of LF component.…”
Section: Introductionmentioning
confidence: 99%